The Effect of Digital Platforms on News Audience Behavior. Issue 5 (28th May 2018) - Nelson, Jacob L.; Lei, Ryan F.
Abstract : Journalism researchers and professionals are increasingly focused on the mobile platform, which many believe has become the most popular method of digital news consumption. However, few studies that examine digital news use draw from observed audience behavior. Furthermore, little is known about whether or not different digital platforms affect how audiences actually attend to news. This article addresses these gaps. Using online audience data, we find that over the past year, the mobile news audience has indeed surpassed the desktop news audience in size, and that a subset of this audience devotes an enormous amount of time to news apps, especially compared with time spent on desktop devices. In light of our findings, we argue the mobile news audience should be seen not as one homogenous mass, but as two distinct groups—mobile news browsers and mobile app users. We conclude by discussing the implications of these findings for news production.